2022
DOI: 10.1111/ajd.13912
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopic findings and histopathological correlation in large cell acanthoma

Abstract: Since large cell acanthoma (LCA) has many overlapping clinical and histopathological features with other epidermal pigmented tumours, an additional method to differentiate it would be of great clinical significance. A retrospective study was performed on 33 lesions (26 patients) to identify distinct dermoscopic findings of LCA and to describe dermoscopic‐histopathological correlations. The results revealed that dermoscopy significantly aids in the distinction of LCA from other epidermal tumours included in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Conversely, Švajdler et al in 2016 examined the presence of α-HPV and β-HPV in extragenital/extraungual Bowen's disease, finding a considerable proportion of lesions positive for high-risk HPV types, which could imply the etiological role of HPV in these precancerous conditions [26]. The literature also discusses the potential benefits of HPV vaccination in preventing NMSC, with some evidence suggesting that a beta-HPV vaccine could serve as an adjuvant treatment measure for patients with recalcitrant NMSC [22,66,67]. The role of HPV proteins in cancer development was explored by Balaji et al in 2022, who reviewed the mechanisms through which HPV proteins, especially E6 and E7 oncoproteins, contribute to carcinogenesis [68].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Švajdler et al in 2016 examined the presence of α-HPV and β-HPV in extragenital/extraungual Bowen's disease, finding a considerable proportion of lesions positive for high-risk HPV types, which could imply the etiological role of HPV in these precancerous conditions [26]. The literature also discusses the potential benefits of HPV vaccination in preventing NMSC, with some evidence suggesting that a beta-HPV vaccine could serve as an adjuvant treatment measure for patients with recalcitrant NMSC [22,66,67]. The role of HPV proteins in cancer development was explored by Balaji et al in 2022, who reviewed the mechanisms through which HPV proteins, especially E6 and E7 oncoproteins, contribute to carcinogenesis [68].…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, LCA may be difficult to be differentiated from a solar lentigo, a pigmented actinic keratosis, or a flat seborrheic keratosis 3 . A recently published study performed on 33 lesions (26 patients) identified distinct dermoscopic findings of LCA 4 . The most frequent dermoscopic findings are a yellow opaque homogenous area, grey/brown dots and globules, a moth-eaten border, white streaks, and a pseudonetwork 2,4 , most of which were also present in this case.…”
mentioning
confidence: 99%
“…A recently published study performed on 33 lesions (26 patients) identified distinct dermoscopic findings of LCA 4 . The most frequent dermoscopic findings are a yellow opaque homogenous area, grey/brown dots and globules, a moth-eaten border, white streaks, and a pseudonetwork 2,4 , most of which were also present in this case. Another study evaluated 13 patients and also identified these as the most frequent dermoscopic features and found that milia-like cysts and white to yellow surface scale were uncommon findings 5 .…”
mentioning
confidence: 99%